Wissen und Einstellungen zu Essstörungen bei Jugendlichen mit türkischem Migrationshintergrund: Potenzielle Implikationen für die Essstörungsprävention = Knowledge and attitudes towards eating disorders among adolescents with Turkish migration background : Potential implications for eating disorder prevention? - Feldhege, Johannes; Moessner, Markus; Bauer, Stephanie (Psychotherapeut, 2019)
BackgroundPoor knowledge (mental health literacy) and stigma are considered key barriers with respect to the utilization of professional help for eating disorders. Both aspects are common targets in the psychoeducative part of prevention programs. It is unclear to what extent such contents should be adapted depending on participants’ migration background.ObjectiveThe present study investigated differences in mental health literacy, stigmatization, and attitudes towards help-seeking for eating disorders between groups of adolescents with and without a migration background.Material and methodsA sample of 139 German adolescents without a migration background and 126 adolescents with a Turkish migration background were surveyed regarding their attitudes towards eating disorders based on a case vignette describing a 16-year-old female student with bulimia nervosa. Participants completed questionnaires on mental health literacy, stigma, anticipated help-seeking behavior and barriers that would prevent them from seeking professional help if needed.ResultsLess than one third of participants identified the condition described in the vignette as an eating disorder. Adolescents with a Turkish migration background stigmatized more than participants without a migration background and recommended professional treatment less frequently. Groups did not differ with respect to their own anticipated help-seeking behavior; however, differences were found concerning specific barriers why adolescents might actually not utilize care when needed.ConclusionThe results have important implications for a target group-specific orientation of prevention programs to the needs of participants based on their migration background.
Online publiziert: 18. Dezember 2018
Gesehen am 22.07.2019